Estudio de pre-factibilidad para la instalación de una planta productora de compotas a base de aguaymanto (Physalis peruviana), camote amarillo (Ipomoea batatas) y quinua blanca (Chenopodium quinoa) - Guerrero Ruiz, Olga Ximena (2020)
The present work seeks to demonstrate the feasibility of a project for the installation of a production plant for compotes based on golden berry, yellow sweet potato and white quinoa, justifying its technical, economic, and social viability. This research has been carried out with the aim of promoting balanced feeding in infants through a homogeneous mixture that provides essential nutritional values for it and avoids suffering from diseases such as Chronic Child Malnutrition (CCM) and anemia due to iron deficiency.